Pengaruh Penyuluhan terhadap Pengetahuan Kesehatan Gigi dan Mulut Santri MTs Kelas IX di Pondok Pesantren Nurul Jadid dan Al-Izza Situbondo - Putri Arifatul Jannah; Kiswaluyo Kiswaluyo; Hestieyonini Hadnyanawati (Pustaka Kesehatan, 2022)
Pondok pesantren are Islamic religious education institutions, pesantrens' students are not allowed to bring communication tools that can cause the lack of knowledge of students, especially about dental and oral health. Eduaction is the provision of information that will increase knowledge. The purpose of study was to determine the influence of education toward knowledge dental and oral health of MTs class IX students at Pondok Pesantren Nurul Jadid and Al-Izza Situbondo. This study used quasi-experimental method with one group pretest and posttest research design. The research subjects was recruited using total sampling technique, as many as 37 students. The measuring instrument of this research used questionnaire. Data analysis used univariate analysis and T test and R2 test. The results showed that as many as 16 students (43%) had poor knowledge before being given education, after being given education there was an increase as many as 37 students (100%) had good knowledge. The results of the T test and R2 test showed that the value of p=0.000 (<0.05) and R2 was 0.086 (86%). The study concluded that there is an influence of education toward knowledge dental and oral health of MTs class IX students at Pondok Pesantren Nurul Jadid and Al-Izza Situbondo and had very strong category of closeness.